Gait Analysis in the 6-Minute Walk Test in Patients with COPD - Jan Szczegielniak; Sebastian Rutkowski; Anna Wdowiak; Katarzyna Bogacz; Jacek Luniewski (Lithuanian Sports University, 2020)
Professional literature provides various studies discussing gait pathologies depending on the type of nervous system and skeletomuscular system. There are, however, no complex studies discussing aspects of gait, such as walking pace, step length or step duration during the 6-minute walk test in patients with COPD. The objective of this work was, therefore, to analyse the gait of patients with COPD during the 6-minute walk test. It attempted to answer the question how gait parameters change during physical effort in case of patients with COPD. The research included 33 in-patients with COPD (27 males and 6 females), with median age of 65.7 ± 10.4, treated in MSWiA Hospital in Glucholazy. For the purposes of gait analysis, the GaitRite mat was used to measure walking pace, step length and step duration. The mat was 4 meters in length and the active surface consisted of 14 thousand sensors. Pearson's correlation index and t test were used to calculate the relationships between the tested parameters. The analysis of the results showed that as the distance covered in the 6-minute walk test increased, the pace of walking decreased and the step duration and length significantly increased (p < 0.05). High correlations between the values of gait parameters and distance covered were observed. The research showed statistically significant differences in the values of parameters indicating walk pace, step duration and step length between the first and the last tests. Keywords: gait analysis, 6MWT, COPD.